2022
DOI: 10.1097/lgt.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Dysplasia After a Loop Electrosurgical Excision Procedure: Local Versus General Anesthesia

Abstract: Objective: This study aimed to compare the rates of positive specimen margins and postconization recurrent dysplasia between loop electrosurgical excision procedures (LEEPs) performed under general anesthesia (GA) and LEEP under local anesthesia (LA).Methods: This retrospective cohort study included all consecutive women who underwent LEEP between 2011 and 2019. Collected data included demographics, LEEP indication, cone dimensions, and margin involvement as well as recurrence rate. Women who had undergone pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…In our study, cone height and volume were close to the ideal cut-off values and were similar between the groups. A recent retrospective study including 146 women who underwent LEEP using GA or LA demonstrated that the type of anesthesia did not affect the surgical margins after the procedure 21 . Similarly, we demonstrated in a multivariate analysis that the mode of anesthesia does not influence the surgical margins.…”
Section: Discussionsupporting
confidence: 74%
“…In our study, cone height and volume were close to the ideal cut-off values and were similar between the groups. A recent retrospective study including 146 women who underwent LEEP using GA or LA demonstrated that the type of anesthesia did not affect the surgical margins after the procedure 21 . Similarly, we demonstrated in a multivariate analysis that the mode of anesthesia does not influence the surgical margins.…”
Section: Discussionsupporting
confidence: 74%
“…The same applies to the diagnosis of an HSIL in the first 2 years after LEEP by biopsy (4.2 % vs. 1.3 %) or repeat LEEP (7.0 % vs. 9.3 %). The authors conclude that the anaesthetic technique of choice for a LEEP should be LA [14].…”
Section: Discussionmentioning
confidence: 96%
“…Gleiches gilt für die Diagnose einer HSIL in den ersten 2 Jahren nach LEEP mittels Biopsie (4,2 % vs. 1,3 %) oder Re-LEEP (7,0 % vs. 9,3 %). Die Autoren folgern, dass für LEEP LA das Anästhesieverfahren der Wahl sein sollte [14].…”
Section: Diskussionunclassified
“…The safety and efficacy of LEEP under local anesthesia have been documented in many studies [6, 7]. Postoperative pain, postoperative bleeding, infection, and the margin status of the resected specimen did not differ significantly between the clients who underwent LEEP under local versus general anesthesia [6–9]. In fact, the local anesthesia group had fewer bleeding complications and higher overall satisfaction [6, 7, 9].…”
Section: Introductionmentioning
confidence: 99%